The New European Union Whistleblowing Directive: In Comparison to Indonesia’s Practice - Hajdú, József; Rahman, Rofi Aulia (Faculty of Law, Hasanuddin University, 2021)
With the European Union Whistleblowing Directive (2019), the topic of whistleblowing is becoming increasingly important for EU MS’s public and private entities. Whistle-blowers might play a vital role in exposing corruption, fraud and mismanagement of the EU’s supranational norms. The Directive introduced minimum standards for the protection of whistle-blowers and obliges many public and private entities to introduce their own internal whistleblowing channels. The EU also can take some lessons from Indonesia about the practice and obstacle in implementing whistleblowing system. The aim of this article is to introduce the new EU Whistleblowing Directive’s main features and some presumable obstacles for implementation. The hypothesis is that the new Directive might enhance the fairwork-place environment, roll back fraud and corruption, reduce work-related wrongdoing and manage equal treatment and no- discrimination policy including bullying and sexual harassment. However, some theoretical and pragmatic discrepancies will be introduced as well.